2016
DOI: 10.1016/j.ijimpeng.2016.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Verification of a theoretical model of tensor skin under water impact by considering the fluid–structure interaction

Abstract: A B S T R A C TTensor skin is a kind of composite sandwich structure developed to improve the helicopter's crashworthiness when it impacts with water. In our previous theoretical studies, by employing the rigid, perfectly plastic idealization and the pulse approximation method, the static and dynamic responses of tensor skin under uniform pressure loading were obtained.In this study, a fluid-structure interaction simulation model of tensor skin impinging with water is established by FE method, in order to veri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Detailed reviews of the studies on water entry problems with application to aerospace structures can be found in [5] and in [6]. In [7] and [8] some problems related to helicopter ditching are examined. The use of computational approaches for the design and certification of aircraft at ditching is of course very attractive, and significant steps forward have been taken recently [9,10,11,12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Detailed reviews of the studies on water entry problems with application to aerospace structures can be found in [5] and in [6]. In [7] and [8] some problems related to helicopter ditching are examined. The use of computational approaches for the design and certification of aircraft at ditching is of course very attractive, and significant steps forward have been taken recently [9,10,11,12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Extensive studies on jet impingement have been conducted [14][15][16]. A fluidstructure interaction simulation model of tensor skin impinging with water has been established using FE method [17,18]. Air jet impingement is a highly effective heat transfer technology, and improving its heat transfer efficiency is important for engineering and industrial applications [19,20].…”
Section: Introductionmentioning
confidence: 99%